Evaluasi Asuhan Kefarmasian terhadap Hasil Terapi dan Kualitas Hidup Pasien Hipertensi Primer di Rumah Sakit - Sitepu, Nadroh Br; Harahap, Urip; Nasution, Salli Roseffi (Jurnal Farmasi Indonesia, 2014)
The management of hypertension ideally requires collaboration between health professionals which includes in the three aspects: medical care, pharmaceutical care, and nursing care. The purpose of this study was to determine the impact of pharmacist counseling conducted on therapeutic outcomes in systolic blood pressure (SBP), diastolic blood pressure (DBP), body mass index (BMI), blood glucose levels (BGL) period, total cholesterol, and quality of life of patients were measured Short-Form Health Survey 36 (SF-36). This study was conducted at RSUD dr.R.M. Djoelham Binjai involved 60 primary hypertensive patients. Patients were divided into two groups: group counseling and with out conseling. Data were analyzed by independent sample t-test. The result of this study showed significant differences in SBP (p=0.048), BMI(p=0.014), BGL(p=0.002) and total cholesterol (p=0.000) and value of quality of life who received counseling (63.17%) and without counseling (54.80%) with p=0.001. But obtained no significant differences between DBP (p=0.068).Keywords : primary hypertension, pharmaceutical care, counseling.